International migration, human capital formation, and saving - Oded Stark; Agnieszka Dorn (University of Tübingen, Faculty of Economics and Social Sciences, 2013)
In the model of Stark et al. (1997, 1998), the possibility of employment in a developed country raises the level of human capital acquired by workers in the developing country. We show that this result holds even when workers have the option to save.
urn:nbn:de:bsz:21-opus-66127
Keywords: D91; F22; J22; J24; 330; Human capital formation; Savings; Intertemporal choice; Prospect of migrating